2017
DOI: 10.1016/j.jvs.2017.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Break Out of the Classroom: The Use of Escape Rooms as an Alternative Learning Strategy for Surgical Education

Abstract: Conclusions: Overall, average LOE remained relatively consistent between 2012 and 2016, with most abstracts classified as level III or IV evidence. There was a gradual albeit minor increase in the average level of evidence in 2016, potentially indicating the increasing commitment to producing and disseminating high-level research in vascular surgery. Furthermore, a lack of a classification tool specific to vascular surgery research occasionally presented a challenge in assigning LOE, perhaps indicating a need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The finding shows that such a model can facilitate knowledge and motivation to learn about healthy nutrition. These findings correspond with other studies' findings, which indicated an increase in participants' knowledge and motivation following participation in educational escape games (e.g., Kinio et al, 2017;Voros & Sarkozi, 2017). The teamwork component, which was found dominant in the EduEG environment as well as in regular escape games environments, correspond with other studies indicated that escape game environments promote collaborations (e.g., Wiemker et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The finding shows that such a model can facilitate knowledge and motivation to learn about healthy nutrition. These findings correspond with other studies' findings, which indicated an increase in participants' knowledge and motivation following participation in educational escape games (e.g., Kinio et al, 2017;Voros & Sarkozi, 2017). The teamwork component, which was found dominant in the EduEG environment as well as in regular escape games environments, correspond with other studies indicated that escape game environments promote collaborations (e.g., Wiemker et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Recently, educational escape games are starting to emerge around higher education curriculums. Medical students experienced educational escape game as an alternative learning strategy for medical education (Kinio, Dufresne, Brandys, & Jetty, 2017), and nursing students experienced escape game toolbox in pharmacology course (Hermanns et al, 2018). Educational escape games are also used to create engaging library instruction sessions in universities (e.g., Mayer & Toates, 2016).…”
Section: Educational Escape Gamesmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the current pandemic (COVID- 19), face to face approach of conducting educational escape rooms are not possible, so that an online delivery model of approach is adopted here. For that a JavaScript Web Interface is developed.…”
Section: Introductionmentioning
confidence: 99%